Can teachers be victims of cyberbullying? - Zăvoianu, Elena-Ancuța; Sun, Kefan (Technium Social Sciences Journal, 2022)
Cyberbullying is a social phenomenon that takes place with the help of technology and that causes suffering to victims. Children being attracted to it and not having enough knowledge about the safe use of technological devices have become potential victims of this phenomenon. In order to prevent and reduce this phenomenon, most researchers have turned their attention to combating online bullying among teenagers. But, they lose sight of the fact that cyberbullying does not take into account gender, age or status and neglect the teachers. According to the few studies on online aggression against teachers, the effects of this phenomenon are similar to those experienced by children, such as: anxiety, depression, low self-esteem, frustration, weight loss, insomnia, somatization, low motivation, and low professional performance. In order to identify the level of victimization among teachers, we conducted a focus group with 12 teachers from primary, secondary and high school education. The analysis of the answers revealed that online aggression against teachers is generally present in middle and high school education and is influenced by digital skills. This article aims to highlight the need to create a positive school climate that helps teachers, students and parents to communicate assertively and develop harmonious relationships. Keywords. cyberbullying, students, teachers, parents, aggression